Messy Bessey's closet - McKissack, Pat, 1944-; Hackney, Rick; McKissack, Fredrick (Chicago : Childrens Press, 1989)
Messy Bessey learns a lesson about sharing when she cleans out her closet.
School Library Journal.
School Library Journal, February 2000.
2.
2.0
K-3
P-2.
Keywords: Cleanliness -- Fiction; Orderliness -- Fiction; Sharing -- Fiction; Stories in rhyme; Cleanliness -- Fiction; Orderliness -- Fiction; Sharing -- Fiction; Stories in rhyme; Readers (Elementary).